Socjologiczne aspekty kryzysu władzy - Czarkowski, Andrzej (Wydział Prawa i Administracji UAM, 1982)
The author of the article makes an attempt to determine social reasons of the Polish power crisis leading to the August conflict of 1980. Some trends of the discussion both inside and outside of the Party are criticized in the introductory remarks, i.e. 1) assumption of premises of the simplified economism, 2) failure to notice the contradictions inherent in the socialist development, 3) reasoning on the faith of the idealistic understanding of an individual's part in the history. Briefly speaking, it is a question of the trend which is a vulgarization of the Marxist theory of social developement. Finally the author formulates a hypothesis of contradictions inherent in socialism, which result in situations of crisis under particular .instances, assuming the shape of sharp social conflicts. Disfunctions of power are considered by the author to be one of those instances. A conflictive crisis of power has been a cyclically occuring phenomenon of the post war Poland in spite of the fact that the rules of the socialist democracy had been already laid down and the institutions of people's democracy were formed. A personality cult which could not have been overcome till August of 1980 was one of the reasons generating the power crisis. It gave rise to the contradictions between the system of the socialist democracy and the antidemocratic technics of power wielding. Inability to solve this contradiction was a result of primitive interpretation of the Leninist proposition of the proletarian dictatorship. A principle of the democratic centralism suffered a vulgar way of understanding as well, what in turn gave rise to the capacity of the executive power to escape a social control. In this way, the legislative, judicial and even the political power became subordinated to the executive machine. And the working masses were becoming an object of power instead of being its subject. At the same time a bureaucratic structure developed to be the actual social power supporting the executive machine. Bureaucracy severed its ties with the working masses of whom it had descended before and whom it was supposed to serve. Simultaneously, new powerful barriers were formed to prevent the penetration of new elements to the power machine. All this favored the generation of permanent formal and non-formal ties inside the bureaucratic structure to facilitate fulfillment of the interests of own stratum. These interests involved legal and illegal acquisition of social and material privileges. The bureaucratic stratum is also getting into an alliance with a lower middle class. Consequently the class interest of bureaucracy conflicted with the one of working masses producing in turn another factor of conflicts: a serious damage to the sense of social justice.
The Sociological Aspects of Power Crisis